2021
DOI: 10.3390/insects12020109
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Sublethal Effect of Farnesyl Acetate on Diamondback Moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae)

Abstract: The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is the most important pest of cruciferous vegetables worldwide. In this study, we evaluated the properties of selected farnesyl derivative compounds against P. xylostella. The toxicity and sublethal concentration (LC50) of farnesyl acetate, farnesyl acetone, farnesyl bromide, farnesyl chloride, and hexahydrofarnesyl acetone were investigated for 96 h. The leaf-dip bioassays showed that farnesyl acetate had a high level of toxicity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 61 publications
3
7
1
1
Order By: Relevance
“…The result indicated that the fluxametamide toxicity to P. xylostella was higher than that of abamectin, spinosad, indoxacarb, chlorantraniliprole and fenoxycarb [21,41,42]. In addition, the second instar larvae of P. xylostella exhibited an LC 50 value of 56.41 mg L −1 when treated with farnesyl acetate, was higher than the present results with a lower toxicity [43]. However, the LC 50 of the technical grade fluxametamide, obtained from the present study, was also lower than that of rac-fluxametamide (1.90 mg L −1 ) and its enantiomers; S-(+)-fluxametamide (0.62 mg L −1 ), or R-(-)-fluxametamide (34.18 mg L −1 ) at 48 h [40].…”
Section: Discussioncontrasting
confidence: 69%
“…The result indicated that the fluxametamide toxicity to P. xylostella was higher than that of abamectin, spinosad, indoxacarb, chlorantraniliprole and fenoxycarb [21,41,42]. In addition, the second instar larvae of P. xylostella exhibited an LC 50 value of 56.41 mg L −1 when treated with farnesyl acetate, was higher than the present results with a lower toxicity [43]. However, the LC 50 of the technical grade fluxametamide, obtained from the present study, was also lower than that of rac-fluxametamide (1.90 mg L −1 ) and its enantiomers; S-(+)-fluxametamide (0.62 mg L −1 ), or R-(-)-fluxametamide (34.18 mg L −1 ) at 48 h [40].…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, fenoxycarb significantly increased the preoviposition period but shortened the oviposition period, compared to the control. Yusoff et al (2021) observed similar effects were observed with farnesyl acetate decreasing oviposition in P. xyllostella. According to Yusoff et al (2021), decreasing oviposition time may led to decreases in fecundity.…”
Section: Discussionsupporting
confidence: 82%
“…Otherwise, it will be difficult to uncover the full sublethal effects of pesticides and their dynamics. While there have been a number of studies investigating the sublethal effects on DBM of various insecticides including spinosad, 26 indoxacarb and hexaflumuron, 14,21 chlorantraniliprole, 18 tebufenozide, chlorfluazuron and indoxacarb, 46 metaflumizone, 47 tolfenpyrad, 48 fenoxycarb 49 spinetoram, 50 and farnesyl acetate, 51 all of these studies found deleterious impacts only. Since sublethal doses below the NOEC were omitted in these studies, people cannot rule out that the above insecticides may actually have hormetic effects.…”
Section: Discussionmentioning
confidence: 99%